New and rare species of the Gamasida (Acari) in the Polish fauna, recorded in ‘Bagno Stawek’ Reserve (Tuchola Forest, northern Poland) - Marquardt, Tomasz; Kaczmarek, Sławomir (Biological Letters, 2010)
As a result of 3-year studies of gamasid mites (Acari) from ‘Bagno Stawek’ Reserve (in the Zaborski Landscape Park), 4 rare species were identified: Platyseius subglaber (Oudemans, 1903), Stylochirus giganteus (Willmann, 1938), Uroobovella minima (Koch, 1841), and Veigaia transisalae (Oudemans, 1902). Among them, S. giganteus is new to the fauna of Poland.